Prevalidation of an ELISA for Detection of a New Clinical Entity: Leishmania donovani-Induced Cutaneous Leishmaniasis - Bhagya Deepachandi; Sudath Weerasinghe; Himali Gunathilake; Thisira P. Andrahennadi; Mahendra N. Wickramanayake; Shantha Siri; Vishvanath Chandrasekharan; Preethi Soysa; Yamuna Siriwardana (International Journal of Analytical Chemistry)
Human leishmaniasis which is considered a neglected tropical parasitic disease presents in three main clinical forms (i.e., cutaneous leishmaniasis (CL), mucocutaneous leishmaniasis (MCL), and visceral leishmaniasis (VL)) that are mainly determined by its causative species. Leishmania donovani, the most virulent and visceralizing parasite, is increasingly reported to cause CL in many countries in the world. Although CL is generally not considered to evoke a humoral immune response except for a nonrobust and a variable response in minority of cases, VL is associated with a clear strong humoral response. However, humoral response in L. donovani-induced CL has not been well evaluated before. A suitable serology-based assay is an essential primary step in such a study. An indirect enzyme-linked immunosorbent assay (ELISA) based on Leishmania promastigote crude antigen (Ag) was designed and optimized in order to utilize in further serological studies on this new clinical entity. Optimization included quantification of crude Ag, checkerboard titration method for determination of optimal concentrations for coating Ag, human sera and secondary antibody (Ab) with suitable coating buffer, blocking buffer, and incubating temperatures. The selected coating buffer was 0.02 M phosphate buffer, pH 6.8, and the blocking buffer was 2% fetal bovine serum with 0.01 M phosphate-buffered saline. At least 1 μg of crude Ag was required for coating the ELISA plate, while 1 : 1000 serum was used as primary Ab. The optimized concentration of secondary Ab was 1 : 64000 which might be altered according to manufacturer recommendations. The assay specificity was pre-evaluated using sera (n = 20 from each category) from confirmed CL patients and controls (other skin diseases which mimic CL, other systemic diseases that mimic VL, nonendemic healthy controls, and endemic healthy controls). This procedure described an optimization procedure of an ELISA technique for detection of anti-Leishmania antibodies in patients with L. donovani caused CL.